2019
DOI: 10.1002/rcm.8485
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of 2‐hydroxyglutarate enantiomers and its lactones by gas chromatography/electron ionization tandem mass spectrometry

Abstract: Rationale 2‐Hydroxyglutarate (2‐hg) exists as enantiomers and can readily undergo cyclization to its lactone. Gas chromatography/electron ionization mass spectrometry (GC/EI‐MS) has been used to separate 2‐hg enantiomers in bodily fluids but the assay cannot simultaneously measure cyclic and acylic 2‐hg enantiomers. Furthermore, the assignment of ion structures was not verified by complementary MS data. Methods GC/EI‐MS and product ion analysis were used to obtain MS and MS/MS spectra of 2‐hg, deuterated and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…R-711, a lactonase that acts on D-2-HG-lactone, has been described, but no lactone formation has been detected [37]. Lactone formation during the derivatization of 2-HG has already been described by others as a side-product of the derivatization reaction or due to the acidification of the sample [21,30,31]. We observed a stable ratio of 4:1 (lactone/2-HG) of the two derivatives when standard solutions were analyzed.…”
Section: -Hg-lactone Is a Novel Endogenous Metabolitementioning
confidence: 99%
See 1 more Smart Citation
“…R-711, a lactonase that acts on D-2-HG-lactone, has been described, but no lactone formation has been detected [37]. Lactone formation during the derivatization of 2-HG has already been described by others as a side-product of the derivatization reaction or due to the acidification of the sample [21,30,31]. We observed a stable ratio of 4:1 (lactone/2-HG) of the two derivatives when standard solutions were analyzed.…”
Section: -Hg-lactone Is a Novel Endogenous Metabolitementioning
confidence: 99%
“…Recently, Strain et al observed non-negligible amounts of R-2-HG-lactone (IUPAC: R-5-Oxo-2-tetrahydro-furancarboxylic acid), the intramolecular ester of R-2-HG (=D-2-HG), in urine specimens from IDH1/2-mutated brain tumor patients after the derivatization of 2-HG with (trimethylsilyl)diazomethane for enantioselective GC-MS analysis [21]. Here, we confirmed the endogenous occurrence of 2-HG-lactone in various biological specimens in the presence of IDH1/2 mutations and investigated possible mechanisms for its formation.…”
Section: Introductionmentioning
confidence: 99%
“…Given that L-2-HG and D-2-HG are related to different acidurias, identification of the enantiomers of 2-HG plays an important role in the diagnosis of these diseases. Different analytical methods for the separation and determination of the enantiomers of 2-HG in urine samples have been reported, including 1 H and 13 C NMR [11], use of potentiometric membrane electrodes [12], HPLC-MS [13,14], GC-MS [15][16][17][18], and CE-MS [19]. However, methods that involve MS systems require tedious sample pretreatment and derivatization steps, long analysis times, and expensive systems.…”
Section: Introductionmentioning
confidence: 99%